Implikasi Teori Psikologi Kognitif dalam Proses Belajar dan Pembelajaran - Magdalena, Ina; Nurchayati, Aan; Uyun, Nur; Rean, Gresia Tuto (Lembaga Yasin AlSys, 2023)
This article aims to analyze the understanding of the flow of cognitive theory in the learning process in learning. Cognitive-psychological processes include how information is obtained, presented and transformed into knowledge that is raised again as a guide in human attitudes and behavior. Learning is a mental or psychological activity that takes place in active interaction with the environment which results in changes in knowledge, understanding, skills, and attitude values. which is relatively permanent. Learning will be more successful if the material studied is meaningful. Active student involvement in each learning syntax is very important because only with active students can the process of assimilation and accommodation of knowledge and experience occur properly.